Performance of Law Enforcement Officials in the Application of Article 33 of Law No. 11 of 2012 in the Vina Cirebon Case - Hamid, Sainul; Sufriaman, Sufriaman; Triyantoro, Andri (Westscience Press, 2024)
This study examines the performance of law enforcement officials in applying Article 33 of Law No. 11 of 2012 within the context of the Vina Cirebon case. Utilizing a qualitative approach, the research employs juridical normative analysis to explore the effectiveness and challenges faced by officials in enforcing the law. The findings reveal varying levels of understanding and awareness of Article 33 among law enforcement officials, impacting the consistency and effectiveness of its application. Key challenges identified include insufficient training and resources, discretionary decision-making, and difficulties in victim participation. Despite the potential benefits of diversionary measures, inconsistencies in their application and a lack of follow-up mechanisms hindered their effectiveness. The study concludes with recommendations for enhancing training programs, standardizing procedures, improving victim engagement, and increasing resources to support the successful implementation of diversion measures. This research contributes to a deeper understanding of the practical implications of legal provisions and offers recommendations for strengthening the juvenile justice system in Indonesia.